(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This paper is a transcript of the table Imprisioned theater: exchanging artistic experiences in prison contexts transmitted by the YouTube platform, on 25th May 2020, in the middle of the Coronavirus Pandemic. The table was composed by thetheater directors Christina Fornaciari, Magno Bucci, Vicente Concilio , Viviane Narvaes and Zeca Nosé and the Judge of Law, João Marcos Buch.